Global Impact of Musical Extracurriculars on Cultural Enrichment: Dampak Global Ekstrakurikuler Musik terhadap Pengayaan Budaya - Solikha, Nurul Lailiyatus; Linggo Wati, Tri (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores how musical extracurricular activities at SD Muhammadiyah 1 Taman foster cultural appreciation and patriotism among elementary students in Indonesia. Using qualitative methods like observation, interviews, and document analysis, the research unveils effective collaboration between stakeholders, student enthusiasm, and character development. The findings underscore the importance of such activities in promoting cultural awareness and preserving local heritage, highlighting the need for continued support and integration in educational curricula. Highlight: Collaborative stakeholders ensure successful musical extracurricular implementation. Activities nurture tolerance, patriotism, and cultural appreciation among students. Integration into curricula vital for preserving and promoting local cultural heritage. Keyword: Musical extracurricular activities, Cultural appreciation, Elementary education, Stakeholder collaboration, Character development